Lower bound on the small displacements of impulsively loaded rigid-plastically anisotropic structures - The, Vu Van (Vietnam Journal of Mechanics, 1983)
New method for estimating the maximum deflections of pulse-loaded isotropic plastic structures had been discribed in [4]. Here this method is extended to anisotropic continua. The general relation for lower bounds on permanent displacement of beams, circular plates and cylindrical shells is derived. The lower bound on maximum deflection of simply supported circular orthotropic plastic plates is obtained.